Two new species of Anatrichis LeConte (Coleoptera: Carabidae: Oodini) from Japan, with notes on the taxonomic position of Oodes infimus Andrewes - Guéorguiev, Borislav; Morita, Seiji (Zootaxa, 2017)
Two new species of the genus Anatrichis LeConte, 1853 are described from Japan, A. morii, sp. n. (type locality: Fukuoka Prefecture, Shimotoubaru) and A. ryukyuensis, sp. n. (type locality: Okinawa Prefecture, Iriomote Island). Relevant diagnostic features of the new species are described, illustrated and compared with those of other species. A new combination is proposed: Anatrichis infima (Andrewes, 1936), comb. n. from Oodes infimus, and a lectotype designation is made for this species. The “indica” group of species is defined to include all the Asiatic congeners.